Additions to the birds of Wallacea. I. Bird recordsfrom smaller islands in the Lesser Sundas - Murray D Bruce (KUKILA, 1987)
During the preparation of The Birds of Wallacea (White & Bruce 1986), some small island records for the Lesser Sundas were unintentionally omitted although originally covered during the initial compilation of locality data. Their exclusion was due to the long and discontinuous preparation of the annotated checklist. Their inclusion here is offered as a first contribution supplementing the checklist data. A few brief annotations have also been included.